Smart Tree Media Innovation for Developing Early Childhood Cognitive Skills - Muji Masiah; Fauzi Fauzi (Journal of General Education and Humanities, 2026)
The Early years of childhood represent a critical phase for cognitive development, requiring appropriate stimulation through meaningful and engaging learning experiences. The use of concrete and play-oriented learning media is considered essential in helping children grasp abstract numerical concepts. This study seeks to explore the implementation of smart tree learning media and examine it is contribution to enhancing cognitive abilities in early childhood. A qualitative descriptive case study approach was used in this research. The study took place at Masyithoh Adiraja Kindergarten and involved 22 children aged 5-6 years. Data were gathered through classroom observations, semi-structured interviews, and documentation, and were analyzed using an interactive qualitative analysis framework. The results reveal that the active participation of smart tree media facilities supports the development of foundational cognitive skills, including number sequencing, quantity recognition, one-to-one correspondence, and basic arithmetic operations. Its interactive and tangible characteristics enable children to engage in exploratory, meaningful learning. These findings suggest that integrating play-based and manipulative media can serve as an effective pedagogical strategy in early childhood education settings.